Liberia : 2008 Article IV Consultation, First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Financing Assurances Review, and Request for Waiver and Modification of Performance Criteria; Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Liberia. (IMF Staff Country Reports; Country Report ;, 2009)
This paper presents the staff report for the combined Liberia's 2008 Article IV Consultation and the first review under the Three-Year Arrangement under the Poverty Reduction and Growth Facility. The international community is supporting the Liberian government's efforts to reform the economy. Increases in international commodity prices have contributed to a significant acceleration in inflation in Liberia, where increases have largely been allowed to pass through to the domestic economy. Liberia has been particularly affected by increases in the price of rice, which accounts for 50 percent of the daily caloric intake of households.